COD Reduction in Petrochemical Wastewater Using the Solar Photo-Fenton Process - Majid Mohadesi; Babak Aghel; Mohammad Hamed Razmegir (Journal of Chemical and Petroleum Engineering, 2021)
Water has been recognized as the most fundamental factor in organisms' lives and the most widely used element in industries, while currently, the world is dealing with water scarcity in many areas. This emphasizes the importance of preventing water contamination as well as returning contaminated water produced by industries to the production and consumption cycle. Yet, the need for environmental protection is a certain principle that is generalized in today's world. This necessity has become more important with the growth of industries and technologies and subsequent contamination. Advanced oxidation technology has been substantially developed in recent decades, becoming increasingly important in the treatment process of industrial wastewaters containing resistant organic materials that cannot be removed through conventional treatment methods to reduce water quality parameters. The present study has examined the chemical oxygen demand (COD) in the synthetic monoethyl amine wastewater prepared by the solar Photo-Fenton process. Principal effective parameters in the advanced oxidation technology, including the processing time, the concentration of hydrogen peroxide ion, the concentration of iron (II) ion, and pH, were investigated by the response surface methodology (RSM) through 30 random experiments using central composite design method (CCD) to optimize reaction conditions. The most sufficient operational conditions were achieved at pH=4, [Fe2+] =2 mM, [H2O2] =20 mM, and t=90 min for the COD removal rate of 77.08%.